DESAIN DAN KARAKTERISASI SIFAT FISIK KEMASAN UNTUK UMKM MAKANAN KERING DI KOTA BOGOR - Cholis, Haikal (Kreator, 2023)
One of the MSME City of Bogor with ketapang seeds as its superior product packs its products in plastic jar packaging and labeled with art paper. Packaging like this has complaints from consumers such as requiring a lot of space during storage, packaging that is easily damaged, lack of information and unattractive product packaging. This is the basis so that research is needed to design packaging into new packaging. The research process begins with extracting information, looking for references, making sketches, testing packaging materials, mock up layouts, 3D designs, packaging mock ups and revisions to produce good packaging. This aims to facilitate marketing activities, improve image, and product sales. From the results of the study, the results of the SWOT analysis were obtained in the form of strengths such as visually attractive packaging, elegant, easy to carry anywhere, weaknesses such as secondary packaging not being able to withstand exposure to very large amounts of water, opportunities such as: facilitating marketing activities, enhancing product image. threats such as: competition with similar products in other regions.